Development of high-power multi-output piezoelectric transformers - Hu, Junhui. (2008)
Piezoelectric transformers have many excellent advantages compared with the traditional electromagnetic transformers. However, the poor power management ability of piezoelectric transformer limited its development greatly. Furthermore, in order to miniaturize the power supply further, it is very necessary to improve the power density of the piezoelectric transformer and make one transformer can supply several different outputs for the system. The main results of this study are summarized as follows. High power piezoelectric transformers with dual and triple outputs were developed and investigated. They operate at the thickness shear vibration mode and are able to provide maximum total output power of more than 160 W with a temperature rise less than 20oC. It is the highest output power of PTs in the world up to now. The maximum efficiency of piezoelectric transformer with dual outputs is 98%. The voltage gains of the two outputs are 0.76 and 0.51 at the frequency of 278 kHz, respectively. The maximum efficiency of piezoelectric transformer with triple outputs is 95.7%. The voltage gains of the three outputs are 0.75, 0.84 and 0.39 at the frequency of 278 kHz, respectively. Compared with most of the other low voltage piezoelectric transformers, these transformers are competitive in practical applications because of the high power, multiple outputs, simple structure and flexibility in design.